Desmatamento, agrotóxicos e intoxicações exógenas: uma abordagem do antropoceno brasileiro - Lima, Thiago Felipe Melo de (2025)
Land cover change is one of the main indicators of the Anthropocene. In Brazil, this conversion, driven by the search for land for agriculture, is a continuous process. Based on the Green Revolution, this is an important sector of the Brazilian economy that generates wealth for a part of the population. However, all this prosperity has great environmental and social costs, the use of pesticides and health problems are examples of these costs. In this work, we analyze three stages of this chain of events: changes in land cover, consumption of pesticides and exogenous poisoning, in addition to their connections. Land cover data was obtained from the MapBiomas database, pesticides annual reports data were obtained from the Brazilian Institute for the Environment and Renewable Natural Resources (IBAMA) database and health data from the National Disease Notification System (SINAN). Starting with an ecological time-series study, environmental and health indicators were built, based on the Federation Units and their year-on-year variations. Despite government efforts, deforestation has never stopped or been reversed; in forty years we have converted an area the size of Chile. All this combined with a significant increase in the consumption of pesticides, with glyphosate, the main product sold, losing space in the total percentage. In addition to positive associations between pesticides and exogenous poisoning in four of the nine states surveyed. The results present a country that still places the development of its agriculture above the well-being of its population and its environment.